2008
DOI: 10.1111/j.1365-2672.2008.03742.x
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal and virucidal activity of the alkalophilic P395D/L241V/T343A mutant of vanadium chloroperoxidase

Abstract: For many disinfection formulations, antimicrobial activity at slightly alkaline pH values is required. To date, only the wild-type vanadium chloroperoxidase has been studied for its antibacterial activity, and only at acidic to neutral pH values. Its antiviral activity (e.g. useful for the cleaning of medical equipment) was not studied before. The observed activity for the alkalophilic P395D/L241V/T343A mutant is an important step forward in the application of this robust enzyme as a component in disinfection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…chloride, hydrogen peroxide and the activity of chlorinating enzymes, must be ‘sufficient’. Dose–response effects of microbially produced reactive chlorine on microorganisms have to our knowledge been investigated only for the haloperoxidase system of Curvularia sp., moulds belonging to the ascomycetes (Hansen et al ., 2003; 2004; 2005; Klebanoff, 2005; Pattison and Davies, 2006; Yap et al ., 2007; Renirie et al ., 2008). The studies show that the Curvularia system ‘has a rapid antimicrobial effect against a broad spectrum of bacteria, yeasts and filamentous fungi’ (Hansen et al ., 2003).…”
Section: Are the Concentrations Of The Bio‐reactive Compound In/on Somentioning
confidence: 99%
“…chloride, hydrogen peroxide and the activity of chlorinating enzymes, must be ‘sufficient’. Dose–response effects of microbially produced reactive chlorine on microorganisms have to our knowledge been investigated only for the haloperoxidase system of Curvularia sp., moulds belonging to the ascomycetes (Hansen et al ., 2003; 2004; 2005; Klebanoff, 2005; Pattison and Davies, 2006; Yap et al ., 2007; Renirie et al ., 2008). The studies show that the Curvularia system ‘has a rapid antimicrobial effect against a broad spectrum of bacteria, yeasts and filamentous fungi’ (Hansen et al ., 2003).…”
Section: Are the Concentrations Of The Bio‐reactive Compound In/on Somentioning
confidence: 99%
“…We hypothesized that carboxyl functionalized multi-walled carbon nanotubes (MWNTs-COOH) can be used to allow generation of H 2 O 2 substrate necessary for the conversion of (Cl − ) into HOCl in the presence of CPO. HOCl has a wide spectrum of activity against a variety of pathogens from spores to bacteria [30,31,36]. Our hypothesis was that H 2 O 2 substrate can be produced through an enzymatic chain reaction at the MWNT interface.…”
Section: Resultsmentioning
confidence: 97%
“…HOCl has a wide spectrum of activity against a variety of pathogens such as spores and bacteria [30,31,36]. Specifically, we are employing a strategy to allow the working enzyme chloroperoxidase (CPO) to use H 2 O 2 produced at a nanosupport interface to convert (Cl − ) into HOCl.…”
Section: Introductionmentioning
confidence: 99%
“…In our study the VCPO of C. inaequalis [Messerschmidt and Wever, 1996] was used to produce hypohalous acid from H 2 O 2 and the halides chloride and bromide. Previous work performed by Renirie et al [2008] showed that VCPO, at pH 8.0, in combination with 0.1 M Br -and 0.01 M H 2 O 2 , resulted in a 1-2 log 10 reduction in the viability of planktonic Staphylococcus aureus and Pseudomonas aeruginosa cells.…”
Section: Discussionmentioning
confidence: 99%
“…The antimicrobial activity of vanadium chloroperoxidase (VCPO) from Curvularia inaequalis has previously been investigated; the enzyme was found to be effective against planktonic bacteria, yeasts, fungi and viruses [Hansen et al, 2003;Renirie et al, 2008], but it has never been tested before on oral bacteria growing in either planktonic phase or biofilms. VCPO is able to catalyze the oxidation of halides (chloride, bromide and iodide) and has been shown to have enzymatic activity in a broad pH range between pH 4.0 and 8.0 with a pH optimum of around 5.5 [Van Schijndel et al, 1993].…”
mentioning
confidence: 99%